2018
DOI: 10.3389/fphar.2018.00452
|View full text |Cite
|
Sign up to set email alerts
|

Metformin Mitigates Fibrosis and Glucose Intolerance Induced by Doxorubicin in Subcutaneous Adipose Tissue

Abstract: Doxorubicin (DX) is a chemotherapeutic drug that is used in clinical practice that promotes deleterious side effects in non-tumor tissues such as adipose tissue. We showed that DX leads to extensive damage in adipose tissue via a disruption in 5′-adenosine monophosphate-activated protein kinase (AMPK) and PPAR-gamma signaling. Thus, we investigated whether co-treatment with the biguanide drug metformin (MET) could prevent the side effects of DX through the activation of AMPK in adipose tissue. The goal of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 46 publications
1
16
1
1
Order By: Relevance
“…Vergoni et al (2016) showed that a single injection of doxorubicin elevated FFA levels into systemic circulation [87]. In contrast, in our study in vitro, lipolysis and ATGL were inhibited by doxorubicin [88].…”
Section: Impacts Of Doxorubicin On Adipose Tissuecontrasting
confidence: 63%
“…Vergoni et al (2016) showed that a single injection of doxorubicin elevated FFA levels into systemic circulation [87]. In contrast, in our study in vitro, lipolysis and ATGL were inhibited by doxorubicin [88].…”
Section: Impacts Of Doxorubicin On Adipose Tissuecontrasting
confidence: 63%
“…Studies demonstrate that metformin increases healthspan and lifespan in mice 25 and in elderly patients, improving glucose tolerance and regulating expression not only of metabolic genes but also collagen and DNA repair-related-genes in muscle and adipose tissue 7 . Moreover, it was recently described that metformin treatment attenuated fibrosis and insulin resistance in adipose tissue caused by doxorubicin treatment in rats 26 . In skeletal muscle, metformin treatment improved the oxidative metabolism in gastrocnemius muscle from mice and reduced muscle injury induced by cardiotoxin 9 .…”
Section: Discussionmentioning
confidence: 99%
“…Finally, MET has not only been used as an anticancer agent on its own, but is also useful as an adjuvant to other cancer chemotherapy agents, notably to reduce the side-effects of DOXO [291].…”
Section: ) Hydrogen Ion Dynamics In Multiple Drug Resistance (Mdr) Imentioning
confidence: 99%